Probing electroweak phase transition in the singlet Standard Model via bbγγ and 4l channels - Wenxing Zhang; Hao-Lin Li; Kun Liu; Michael J. Ramsey-Musolf; Yonghao Zeng; Suntharan Arunasalam (Journal of High Energy Physics, 2023)
Abstract We investigate the prospects for resonant di-Higgs and heavy Higgs production searches at the 14 TeV HL-LHC in the combination of bbγγ and 4l channels, as a probe of a possible first order electroweak phase transition in real singlet scalar extension of the Standard Model. Event selection follows those utilized in the bbγγ and 4l searches by the ATLAS Collaboration, applied to simulation using benchmark parameters that realize a strong first order electroweak phase transition. The output of discriminant analysis is implemented by numerical calculation, optimised by the joint restriction from the two channels. The prospective reach for bbγγ/4l channel could be more competitive in probing the electroweak phase transition at lower/higher resonance masses. With 3 ab −1 integrated luminosity, the combination of the bbγγ and 4l channels can discover/exclude a significant portion of the viable parameter space that realizes a strong first order phase transition when the resonance mass is heavier than 500 GeV.